Fiber Concentration on Fermentation of Cleome Gynandra L Based on Storage Time and Solvent Change - Lily Restusari; Ayu Komala Dewi; Alinea Dwi Elisanti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Cleome gynandra L (CGL) or Maman plant, is the basic ingredient of Malay food in Riau Province, Indonesia. The young leaves and stems of CGL are processed into fermented food (Joruk Maman). It contains crude fiber and is useful for lowering blood cholesterol levels. However, effective storage of this CGL has not been carried out. This study wants to see the effect of storage time and solvent change on the fiber content of Joruk Maman. An experimental study applied a completely randomized design (CRD) using 5 groups and 2 repetitions. This sample of CGL leaves was taken from one seller in the Rokan Hilir market of Riau Province. The primary outcome was a difference to the number of fibers in Joruk Maman without solvent change (p =0.001) and with solvent change (p = 0.001) based on the day group and there was no difference base on the temperature group. Secondary outcome was the difference in duration time to produce the highest fiber content at room temperature with the solvent change and not. The highest fiber content occurred at 5 days of storage at room temperature without solvent changing. Meanwhile, by changing the solvent, the fiber content would be optimal for 1-day of storage.